2022
DOI: 10.1186/s12879-022-07905-2
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 vaccination side effects among the child age group: a large cross-sectional online based survey in Saudi Arabia

Abstract: Background Multiple vaccines have been tested in clinical trials for their efficacy and safety. In Saudi Arabia, Pfizer–BioNTech or Moderna were approved for children, however, previous studies to report their safety profile are limited. This research aims to understand the side effect of children's vaccination against SARS-CoV-2 infection in Saudi Arabia. Methods This was an observational retrospective cross-sectional study was conducted using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is similar to the findings of a recent study from Saudi Arabia where parents who intended to vaccinate themselves (OR: 0.599, 95% CI: 0.367–0.980) and who trust the healthcare system (OR: 0.527, 95% CI: 0.327–0.848) reported greater acceptance of children’s vaccination [ 18 ]. In our previous study, the majority of parents strongly agreed (23.4%) and agreed (35.1%) about the importance of getting their children vaccinated, 22.1% of parents strongly agreed, and 33.3% agreed regarding their willingness to get their children vaccinated to prevent coronavirus disease [ 23 ]. Parents who had the COVID-19 vaccine were about five-fold more likely to vaccinate their children compared with parents who did not receive the vaccine (OR = 4.9, CI: 3.12–7.70) in a study from EMR [ 24 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is similar to the findings of a recent study from Saudi Arabia where parents who intended to vaccinate themselves (OR: 0.599, 95% CI: 0.367–0.980) and who trust the healthcare system (OR: 0.527, 95% CI: 0.327–0.848) reported greater acceptance of children’s vaccination [ 18 ]. In our previous study, the majority of parents strongly agreed (23.4%) and agreed (35.1%) about the importance of getting their children vaccinated, 22.1% of parents strongly agreed, and 33.3% agreed regarding their willingness to get their children vaccinated to prevent coronavirus disease [ 23 ]. Parents who had the COVID-19 vaccine were about five-fold more likely to vaccinate their children compared with parents who did not receive the vaccine (OR = 4.9, CI: 3.12–7.70) in a study from EMR [ 24 ].…”
Section: Discussionmentioning
confidence: 98%
“…Intention to take the COVID-19 vaccine was low among patients with chronic diseases, to achieve herd immunity, in a Nigerian study [ 22 ]. Another study from Saudi Arabia showed that the smoking status of the parents, having an allergy, and having other comorbidities were risk factors of having persistent post-COVID-19 symptoms ( p ≤ 0.05) among child age groups [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them (78.9%) said that adverse effects began one day after receiving the immunization, and 65.7% reported that they lasted one to three days. In addition, the most documented effect was pain at the injection site (15.3%) [33]. The World Health Organization (WHO) stated that COVID-19 vaccines, like other vaccines, could cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported symptoms were injection site pain, fatigue, fever, and headache. There were no serious adverse events, and symptoms improved within 1–3 days after vaccination [ 192 ]. Another study from Saudi Arabia reported that 60% of adolescents had at least one side effect post-vaccination.…”
Section: Strategies For Preventing Perinatal Covid-19mentioning
confidence: 99%